Wisdom Has Built Her House (Proverbs 9, 1–6). The History of the Notion in Southern and Eastern Slavic Art in the 14th–16th Centuries) - Brzozowska, Zofia (Studia Ceranea, 2015)
Sophia’s banquet (Divine Wisdom’s banquet) – this type of iconography is an illustration of a specific passage of the ninth chapter of the Old Testament Book of Proverbs: Wisdom hath built herself a house (Prov 9, 1-6). That text became widespread in Old Russian literature within liturgical books containing passages of the Old Testament. Also the comment of Anastasius Sinaites for Proverbs 9, 1-6 was translated into Old Church Slavonic. Iconographic images of the Wisdom’s banquet scene should be considered as a phenomenon typical of South Slavic wall paintings from the period of fourteenth century. Later on, the discussed motif became popular in Old Russian art and began to appear on the East Slavic icons.